(untitled) (Revista Brasileira de Estudos da Homocultura, 2024)
This article aims to investigate the relationship between a narrative closure and the normativization of bodies in films. In this sense, this article will be divided into two parts. The first one is going to discuss how closure is used to adjust a character into the current social norms of gender. For that, I will analyze the films This Must Be the Place (Paolo SORRENTINO, 2011) and The Danish Girl (Tom HOOPER, 2015). The selection of these movies takes into consideration characters who are introduced to the audience as non-normative, but are brought into a certain normativization in the end. The second part of the article intends to bring an example of a movie in which the openness of closure allows the character to maintain a non-normative subjectivity. In this case, the film chosen to be analyzed is the Argentinian XXY (Lucía PUENZO, 2007). My hypothesis is that, by the intrinsic characteristics of closure, which is, according to Susan Hayward, that "the narrative must come to a completion", the necessity of bringing any resolution for the fact that a character does not fit the norm ends up by reinforcing the normativization of the very same characters who are intended to be non-normative. Although narrative closure may be used as a form of coping with social norms, XXY functions as an instance that this is not always necessarily the case. Keywords: Affective-performative cinema. Queer theory. Closure.